(x+5)-(8x-2)=0

Simple and best practice solution for (x+5)-(8x-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+5)-(8x-2)=0 equation:


Simplifying
(x + 5) + -1(8x + -2) = 0

Reorder the terms:
(5 + x) + -1(8x + -2) = 0

Remove parenthesis around (5 + x)
5 + x + -1(8x + -2) = 0

Reorder the terms:
5 + x + -1(-2 + 8x) = 0
5 + x + (-2 * -1 + 8x * -1) = 0
5 + x + (2 + -8x) = 0

Reorder the terms:
5 + 2 + x + -8x = 0

Combine like terms: 5 + 2 = 7
7 + x + -8x = 0

Combine like terms: x + -8x = -7x
7 + -7x = 0

Solving
7 + -7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -7x = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -7x = 0 + -7
-7x = 0 + -7

Combine like terms: 0 + -7 = -7
-7x = -7

Divide each side by '-7'.
x = 1

Simplifying
x = 1

See similar equations:

| 17-2y=19 | | -(2/7)y=(3/14)-(5/14) | | 8x=-25+3x | | 4p*2q^2*3p= | | 3p-30/3=2 | | 6h(x^3-4)-(4-x^3)=0 | | 2x-29/4=4 | | 4a=2+a | | 0,4(3-x)-0,7(x+2)=3,1 | | x^3=1/125 | | 8(x-3)=-3x+86 | | 10r^2-10r+6.4=0 | | x+3x=x+9 | | -72=-18x-6 | | -8w+6(w+2)=14 | | r^2-7r=24-2r | | 7/-4i | | (X*x)-((19-x)*(19-x))=38 | | 2xsqaured+y=3x-1 | | 3m^2-3m-4=0 | | 10+24x^2-16x=3 | | x^2+28x-34=0 | | 4(20)=2(20)+40 | | -3(2s-4)-12=-2(75+1)-3 | | e^3x=17 | | 15+7a=99 | | 120/((30-29)*5) | | (20/2)*3=30 | | x-2.18=2.24 | | 2g(g+6)=0 | | 3*sin(2*x)=-2 | | -6(-2.8)-28=4(-2.8) |

Equations solver categories